2013
DOI: 10.1002/bdra.23211
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cardiac anomalies in VACTERL association

Abstract: Although this study does not, by design, provide further evidence toward the questions of whether CHD is a defining feature of VACTERL association, the frequency of CHD in our cohort does lend support to it being an important medical consideration in patients with VACTERL association. Based on our experience, we strongly recommend a screening echocardiogram to evaluate for CHD in individuals with a potential diagnosis of VACTERL association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…and vascular ring. 210 Prenatal ultrasound findings VACTERL association is the most commonly recognized, nonchromosomal condition in fetuses with congenital heart defects and extracardiac anomalies (23%). 10 In a European study of 2454 fetal cardiac anomalies, among those with VATERL association (N = 15), complex cardiac anomalies represented one-third, a frequency higher than seen in newborns and children.…”
Section: Postnatal Phenotypementioning
confidence: 99%
“…and vascular ring. 210 Prenatal ultrasound findings VACTERL association is the most commonly recognized, nonchromosomal condition in fetuses with congenital heart defects and extracardiac anomalies (23%). 10 In a European study of 2454 fetal cardiac anomalies, among those with VATERL association (N = 15), complex cardiac anomalies represented one-third, a frequency higher than seen in newborns and children.…”
Section: Postnatal Phenotypementioning
confidence: 99%
“…VACTERL association, which was the most common, has been associated with a variety of heart defects, including BAV and conotruncal defects, but was not typically been associated with AoD in large series of patients. 36 Likewise, Schimke immuno-osseous dysplasia, which was present in two patients in this cohort, has not been routinely associated with AoD, but rather with vascular disease secondary to impaired vascular elastogenesis. 37 Given the single occurrence of the remaining conditions, a direct link is difficult to establish.…”
Section: Discussionmentioning
confidence: 66%
“…Recent publications showed association between chromosomal microduplication at 22q11.21 and VACTERL (acronym for Vertebral anomalies, Anorectal malformation, Cardiovascular anomalies, TracheoEsophageal fistula, Renal and/or Radial anomalies and Limb defects) . Here, we present a first‐time prenatally diagnosed fetus carrying a 2‐Mb duplication at 22q11.21 or arr (hg19)22q11.21(18,896,972‐20,959,043)x3 , showing a highly complex heart anomaly consisting of TGA, PA, VSD, and DORV, compatible with VACTERL association . Prieto et al discovered suchlike and reported two cases of supernumerary der22 syndrome, yielding duplication of 11q and phenotypic overlap with VACTERL, including a large secundum artrial septal defect (ASD), VSD, and patent ductus arteriosus (PDA).…”
Section: Discussionmentioning
confidence: 96%